Tautinė tapatybė lietuvių biografijose (Jonas Basanavičius, Jonas Šliūpas, Vincas Kudirka) - Šeferis, Vaidas (Literatūra, 2015)
The article deals with the autobiographic and biographic texts of three most important authorities of the Lithuanian national revival at the end of the 19th and the beginning of the 20th century: Jonas Basanavičius, Jonas Šliūpas and Vincas Kudirka. The goal of the analysis is to capture significant moments in the evolution of the national Lithuanian identity becoming a part of the personal identity by Basanavičius, Šliūpas and Kudirka and also to compare their autobiographic self-images with those provided by later biographical texts. The article shows not only that Basanavičius, Šliūpas and Kudirka represent very different forms of the national self-consciousness, but also that there are large differences between autobiographical and biographical interpretations of the national identity.